2006
DOI: 10.1002/elps.200500651
|View full text |Cite
|
Sign up to set email alerts
|

Toward high sequence coverage of proteins in human breast cancer cells using on‐line monolith‐based HPLC‐ESI‐TOF MS compared to CE MS

Abstract: A method is developed toward high sequence coverage of proteins isolated from human breast cancer MCF10 cell lines using a 2-D liquid separations. Monolithic-capillary columns prepared by copolymerizing styrene with divinylbenzene are used to achieve highresolution separation of peptides from protein digests. This separation is performed with minimal sample preparation directly from the 2-D liquid fractionation of the cell lysate. The monolithic column separation is directly interfaced to ESI-TOF MS to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…One of the main uses of CE-MS in proteomics/peptidomics research is protein identification through the analysis of the peptides produced after enzymatic digestion of the biopolymer [101], including the study of protein modifications [102]. In this regard, an important limitation arises from the frequent generation of unexpected peptidic fragments during the enzymatic digestion of any protein.…”
Section: Ce-ms Using Bare Fused-silica Capillariesmentioning
confidence: 99%
“…One of the main uses of CE-MS in proteomics/peptidomics research is protein identification through the analysis of the peptides produced after enzymatic digestion of the biopolymer [101], including the study of protein modifications [102]. In this regard, an important limitation arises from the frequent generation of unexpected peptidic fragments during the enzymatic digestion of any protein.…”
Section: Ce-ms Using Bare Fused-silica Capillariesmentioning
confidence: 99%
“…The method was developed toward high sequence coverage of proteins originated from a cancer cell lysate, which was subjected to a preparative liquid‐phase IEF in a first step of the whole protocol. Each obtained fraction was separated on an analytical particle packed column and then the individual fractions were digested and analyzed on a PS‐DVB capillary . The suggested HPLC‐ESI‐TOF‐MS method was robust and provided improved loadability compared to a tested CE‐MS method, which was subsequently used for the analysis of the digested peptides.…”
Section: Monolithic Clc‐msmentioning
confidence: 99%
“…In order to enlarge this knowledge and to identify novel drug targets, performing omics experiments is a powerful strategy for the generation of comprehensive data sets for the unbiased study of molecular and functional differences between selected tumor cell populations [ 32 , 33 , 34 , 35 , 36 ]. Despite the broad range of CSC markers, comparison of different CSC populations in the studies mentioned above showed only limited overlap between the populations.…”
Section: Introductionmentioning
confidence: 99%